2021
DOI: 10.3389/fimmu.2021.642166
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota in Common Chronic Inflammatory Disorders Affecting Children

Abstract: The incidence and prevalence rate of chronic inflammatory disorders is on the rise in the pediatric population. Recent research indicates the crucial role of interactions between the altered intestinal microbiome and the immune system in the pathogenesis of several chronic inflammatory disorders in children, such as inflammatory bowel disease (IBD) and autoimmune diseases, such as type 1 diabetes mellitus (T1DM) and celiac disease (CeD). Here, we review recent knowledge concerning the pathogenic mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 479 publications
(571 reference statements)
0
8
0
Order By: Relevance
“…The gut microbiome has also been implicated in many medical conditions, some of which are associated with comorbid pain. These include degenerative 116 and inflammatory joint diseases, 117,118 neurologic conditions including Parkinson’s disease 16 and multiple sclerosis, 30 inflammatory bowel diseases, 119,120 and others. We have limited the scope of this review to include mainly primary pain conditions; however, interested readers may find further reading in the references.…”
Section: Gut Microbiome and Painmentioning
confidence: 99%
“…The gut microbiome has also been implicated in many medical conditions, some of which are associated with comorbid pain. These include degenerative 116 and inflammatory joint diseases, 117,118 neurologic conditions including Parkinson’s disease 16 and multiple sclerosis, 30 inflammatory bowel diseases, 119,120 and others. We have limited the scope of this review to include mainly primary pain conditions; however, interested readers may find further reading in the references.…”
Section: Gut Microbiome and Painmentioning
confidence: 99%
“…Probiotics are living microorganisms that have a positive effect on gut microbiota. Changes in gut microbiota associated with probiotics intake have been shown to have positive effects in a number of diseases, mainly associated with chronic inflammation and oxidative stress [29][30][31][32][33][34], but to date, there have not been many studies on probiotic impact on uterine leiomyoma-only an indirect role of intestinal microflora changes resulting from yoghurt consumption and their effect on myoma formation has been observed [13,17,20,21].…”
Section: The Influence Of Intestinal Dysbiosismentioning
confidence: 99%
“…Previous studies have shown that B. fragilis accounted for 50% of the pathogenic bacteria in neonatal bacteremia ( Brook, 1990 ). Also, some studies have noted that the increased abundance of Bacteroides can cause chronic inflammatory effects and lead to the development of type 1 diabetes mellitus (T1DM), celiac disease and other diseases ( Torun et al, 2021 ). In our study, Bacteroides were more abundant in the case group, which may cause intestinal inflammation most likely due to the increase of harmful bacteria B. fragilis .…”
Section: Discussionmentioning
confidence: 99%